The urban DIBAO programme in China: Targeting and its effect - Yang, Lu (2013)
In this paper, the data of China's Urban Employment and Social Protection Survey 2010 (CULS3) has been adopted to evaluate the dibao programme in China through the use of the RD and matching methods. The analysis of the programme leads to the following conclusions. Firstly, the dibao programme has limited effectson alleviating poverty as per the available data. This may be due to the dibao programme's mis-targeting. Secondly, the health status and living condition of a household are the factors affecting dibao programme's targeting. Thirdly, the dibao programme may change the expenditure behaviour of a household, but since the subsidy offered under this programme would lead to a reduction in the food expenditurre rate of a poor household, the Chinese government ought to provide food coupon not merely cash transfer to the poorest household to help them avoid facing a food shortage. - Reproduced.
Keywords: Living standards - China; Living standards